Relationship between volatile components, antimicrobial and antioxidant properties of the essential oil, hydrosol and extracts of Citrus aurantium L. flowers - Huseyin Değirmenci; Hatice Erkurt (Elsevier, 2020)
Introduction: In the Mediterranean Region, essential oil, hydrosol, and ethanol extract of C. aurantium flowers have a long history of usage in different products such as a flavoring agent and an ingredient of many traditional anti-infectious and skin care products. The present study was undertaken to compare the antimicrobial activity, antioxidant activity and phytochemical composition of essential oil (EO), hydrosol and ethanol extract of Cyprus Citrus aurantium L. flowers. Method: The chemical composition of samples was determined by GC/MS. The total phenolic and flavonoid contents were determined by Folin-Ciocalteu colorimetric method and aluminum chloride colorimetric assay, respectively. Antioxidant activity was evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2). The antimicrobial activity of the samples was determined by disc diffusion and broth microdilution methods against five foodborne pathogenic bacteria. Result: The EO and ethanol extract showed significant antimicrobial activity against all tested pathogens which were attributed to the presence of important phytochemical classes such as polyphenols, flavonoids, alkaloids, and terpenes. The EO showed higher antimicrobial activity followed by ethanol extract with minimum inhibitory concentrations ≤1562 mg/l and ≤6250 mg/l, respectively, against Amoxycillin resistant Bacillus cereus and other test organisms. Significantly (p ≤ 0.05) the higher total phenolic (81.37 mg GAE/g) and flavonoid contents (20.34 mg QE/g) were obtained in the ethanol extract with the higher antioxidant activity as compared to EO and hydrosol with half maximal inhibitory concentration (IC50) values of 96.07 μg/ml in the DPPH and 66.50 μg/ml in the H2O2 assay. A significant correlation (R2 ≥ 0.94) was found between phenolic content and IC50 values for DPPH and H2O2 assays. β-Cholesta-5,22-dien-3-ol, herboxide isomer and isochiapin-B are reported for the first time for essential oil. Conclusion: Citrus aurantium L. flowers have strong potential for the isolation of antimicrobial and antioxidant agents for further use in food and medicine industries as natural preservatives. Keywords: Citrus aurantium L., Foodborne pathogen, Bioactive phytochemicals, Phenolic compounds, Minimum inhibitory concentration (MIC)